KEANEKARAGAMAN JENIS BURUNG PADA BERBAGAI TIPE HABITAT BESERTA GANGGUANNYA DI HUTAN PENELITIAN DRAMAGA, BOGOR, JAWA BARAT - Asep Saefullah; Abdul Haris Mustari; Ani Mardiastuti (Department of Forest Resources Conservation and Ecotourism - IPB University, 2015)
Dramaga Research Forest, located in the outskirt of Bogor, provides a good habitat for birds. This research was aimed to study bird diversity, identifying habitat characteristics (around the forest path, along house edge, riparian habitat and the interior area) and recorded the activities of the local people around the forest. Point count, MacKinnon list, habitat profiling and interviews were conducted. The highest index of species diversity (Shannon-Wiener index) was at interior area (2.34), followed by around the forest path (2.21), along house edge (1.97) and riparian habitat (1.86). The highest species richness was at riparian habitat (27 species), the forest path had 21 species, along house edge had 26 species, while the interior area was a home for 21 bird species. The highest similarity (0.81) was between forest path and interior area. On the activities of the local people, the most often was firewood harvesting. Other activities were hunting for cage birds, harvesting ferns, harvesting wild fruit and harvesting ant larvae. Activity that might disrupt the bird population was hunting. Keywords: Diversity,Dramaga Research Forest, human activities.